Respuesta :

Answer:

  [tex]\lim_{x \to 64} (\frac{x+x^{\frac{1}{2} } +x^{\frac{1}{3} }-76}{x^{\frac{1}{2} } } } )[/tex]   =  0

Step-by-step explanation:

Explanation:-

Given

         [tex]\lim_{x \to 64} (\frac{x+x^{\frac{1}{2} } +x^{\frac{1}{3} }-76}{x^{\frac{1}{2} } } } )[/tex]

       =   [tex](\frac{64+(64)^{\frac{1}{2} } +(64)^{\frac{1}{3} }-76}{(64)^{\frac{1}{2} } } } )[/tex]

      =  [tex](\frac{64+(8^{2} )^{\frac{1}{2} } +(4^{3} )^{\frac{1}{3} }-76}{(8^{2} )^{\frac{1}{2} } } } )[/tex]

      =    [tex]\frac{64+8+4-76}{8} = \frac{0}{8} = 0[/tex]

Final answer:-

[tex]\lim_{x \to 64} (\frac{x+x^{\frac{1}{2} } +x^{\frac{1}{3} }-76}{x^{\frac{1}{2} } } } )[/tex]   =  0